The level of customer participation in co-production of planning the furniture services - Tijūnaitienė, Rigita; Šidlauskienė, Jelena; Petukienė, Evandželina (Business, Management and Economics Engineering, 2010)
This article analyses customer’s level of participation in co-production of service. A client’s, known as a co-producer’s involvement is a pretty new conception of participation in creation of service where customers participate in projects, in direct, all-round and not only physical ways, together with professional representatives of service providers. A customer’s activity is becoming an important factor in order to achieve the results of effective creation of service, considering that client’s level while participating plays an essential role in the creation of service. To accomplish an empirical investigation, two quality methods were selected (observation and interview), which were performed in the company, which provides the services of furniture design. Theoretical literature analyses showed that there are three levels of customer’s participation: low, average and high, which usually appear in creation of co-productive service. Empirical investigation reve-aled that while co-producing services of furniture design customer’s level of participation can be: low, average, average high and high. This shows that “pure” level of participation in co-production of furniture design service appears rarely, while intermediate (“impure”) level of participation can be observed more frequently. It is established that customer’s personality, temper, stress, lack of designer’s attention, preliminary decisions, and goods peculiarities determine causes of customer’s involvement/ devolvement. It is established that it is hard to elucidate and reveal customer’s needs, wishes and motives when the level of participation in co-production of furniture design service is low, and, as a result of that, a chance that the results of a service could not correspond to all customers expectations, rises. It is established that co-production of furniture design service is effective when the level of participation in co-production of furniture design service is average and average high, because high-desired customer’s level of activity has not been noticed. Results of empirical investigation confirmed that in investigated (furniture design) service, high level of participation results in creation of co-productive and effective service, and received result absolutely corresponds to customer’s needs and wishes. After summarizing the results of an investigation, it was noticed that it is possible to expect higher customer’s level of participation if customer’s participation is properly managed. Article in Lithuanian. Klientų įsitraukimo bendrai kuriant baldų projektavimo paslaugas laipsnis